2010
DOI: 10.1103/physrevlett.105.055503
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Predominance of Cementite among Iron Carbides in Steel at Elevated Temperature

Abstract: A long-standing challenge in physics is to understand why cementite is the predominant carbide in steel. Here we show that the prevalent formation of cementite can be explained only by considering its stability at elevated temperature. A systematic highly accurate quantum mechanical study was conducted on the stability of binary iron carbides. The calculations show that all the iron carbides are unstable relative to the elemental solids, -Fe and graphite. Apart from a cubic Fe 23 C 6 phase, the energetically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 31 publications
6
71
0
Order By: Relevance
“…7,[32][33][34][35][36][37][38][39][40][41][42] To the best of our knowledge, all first-principles calculations have been carried out only for Fe 3 C, and a very few attempts have been made to predict its stability and understand mechanical properties of multi-component cementite. Only recently, Jang et al 40 reported the effect of Si on the stability of Fe 3 C. The crystal structure of cementite, Fe 3 C, is well established.…”
Section: Introductionmentioning
confidence: 99%
“…7,[32][33][34][35][36][37][38][39][40][41][42] To the best of our knowledge, all first-principles calculations have been carried out only for Fe 3 C, and a very few attempts have been made to predict its stability and understand mechanical properties of multi-component cementite. Only recently, Jang et al 40 reported the effect of Si on the stability of Fe 3 C. The crystal structure of cementite, Fe 3 C, is well established.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and efficient computational schemes for the theoretical prediction of parameter-free atomic forces and force constants are an essential prerequisite for many applications within first-principles materials design, such as lattice vibrations (phonon spectra, vibronic entropies, phase transitions) [1][2][3][4][5][6][7][8][9][10][11][12][13], diffusion processes (vacancies, impurities, etc.) [14], strain fields (e.g.…”
mentioning
confidence: 99%
“…[1,2] But, it was also noticed that -Fe 2 C is the only carbide forming up to 520 K (250°C) and forms along with cementite till 600 K (330°C) and that it acts as a precursor for the formation of Fe 5 C 2 : [3,4] A long aging study at 300 K (30°C) followed by a brief 405 K (130°C) anneal showed the presence of both g-Fe 2 C and -Fe 2 C: [5] -Fe 2 C is a nonstoichiometric carbon deficient structure of g-Fe 2 C: It was recently shown that -Fe 2 C is only slightly more unstable than g-Fe 2 C and that it can relax to the latter structure. [6] Above 720 K (450°C), it has been observed that Fe 3 C forms exclusively. [1,2] Roughly, the carbides seem to precipitate in the order g-Fe 2 C; Fe 5 C 2 ; and Fe 3 C with increasing temperature [6,7] with the appearance of -Fe 2 C preceding g-Fe 2 C: Both kinetic and thermodynamic factors could be responsible for this observation.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Above 720 K (450°C), it has been observed that Fe 3 C forms exclusively. [1,2] Roughly, the carbides seem to precipitate in the order g-Fe 2 C; Fe 5 C 2 ; and Fe 3 C with increasing temperature [6,7] with the appearance of -Fe 2 C preceding g-Fe 2 C: Both kinetic and thermodynamic factors could be responsible for this observation. But the predominance of each of the carbide in a definite temperature range has been attributed to the lowering of its free energy (and hence stabilization) with temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation